Esophagomediastinal fistula due to secondary esophageal tuberculosis: report of two cases - Nie, Dan (J Int Med Res, 2021)
Esophageal tuberculosis is rare among digestive system diseases. We herein present two cases of esophageal tuberculosis. One patient presented with a choking sensation and pain in the chest, and the other presented with loss of appetite and emaciation. Both patients had an esophagomediastinal fistula, underwent endoscopic ultrasonography and fine-needle aspiration, were clinically diagnosed with esophageal tuberculosis, received antituberculosis treatment, and exhibited clinical improvement. These two rare cases suggest that the possibility of esophageal tuberculosis should be considered in patients with an esophagomediastinal fistula. Endoscopic ultrasonography and fine-needle aspiration can be performed to assist the diagnosis. Good clinical results can often be achieved with timely antituberculosis treatment.